(untitled) (Health Renaissance, 2017)
Backgroud: The optimal method of humeral shaft fracture fixation remains in debate. With the dramatic success of intramedullary fixation for fractures of the femur and tibia, there was speculation that IM-ILN might be more appropriate for humeral shaft fractures than DCP. There are very few studies comparing intramedullary interlocking nail and dynamic compression plating in fracture shaft of humerus and virtually no study in this part of world. Objective: The aim of the study was to assess the fixation of fracture shaft of humerus with interlocking nail and in terms of duration of operating time, amount of blood loss, rate of infection, pain at the fracture site,time to achieve union, functional outcome (DASH score), complications of surgery. Method: This was respective interventional study. All patients with fractures of shaft of humerus that met the criteria for operative interventions (intramedullary interlocking nail) presenting to the department of Orthopaedics BPKIHS over a period of 3 years from July 2006 to August 2009 and giving informed consent were included in the study. The study enrolled 30 patients. Result: Among 30 patients, 75% were male and 25% were female. The mean age of patients was 34.5 years. The usual mode of injury were road trafiic accident followed by fall from height, work place injury. Most of the patients were right handed. The operating time was 100 mins with standard deviation of 11.24. The mean blood loss was 148.75 with standard deviation of 36.70. Post operative hospital stay was 4.5 days. The peroperative radial nerve palsy was 4%. Radiologically, four cortices union was only 50% in 24 weeks post operative time. Dash score gradually improved in susequent followed up. Conclusion: It is concluded that dynamic compression plating is better in our study for fracture shaft of humerus. Plate osteosynthesis remains the gold standard of fixation for humeral shaft fractures. Health Renaissance 2015;13(2): 153-159